INVESTIGATION OF THE ROLE OF HISTOGRAM ANALYSIS IN THE DIFFERENTIAL DIAGNOSIS OF INFECTIOUS AND AXIAL SPONDYLOARTHRITIS-RELATED SACROILIITIS - Uslu, Emine Yıldırım; Yıldırım, Mustafa; Balin, Şafak Özer; Alkan, Gökhan; Gülkesen, Arıf; Akgol, Gurkan; Uslu, Muhammed Fuad (My University, 2025)
Aim: It is not easy to differentiate Brucella sacroiliitis from axial spondyloarthritis (axSpA)-related sa-croiliitis using conventional magnetic resonance imaging (MRI). Histogram analysis, a new tech-nique, is considered useful for differential diagnosis. This study aimed to investigate the role of MRI histogram analysis in the differential diagnosis of Brucella sacroiliitis and axSpA-related sacroiliitis. Material and Methods: This study included 25 patients with axSpA-related sacroiliitis and 25 patients with sacroiliitis secondary to brucellosis. Histogram analysis of the sacroiliac MRI images of the pa-tients was performed on inflammatory areas detected on the T2 fat-suppressed sequence. Ten per-cent, 90 percent, entropy, kurtosis, maximum, mean, median, minimum, skewness uniformity, and variance values were measured. The values obtained were compared between the groups. Results: There was a statistically significant difference between the 10 percent, median, and mini-mum values (p=0.018, p=0.029, p=0.002, respectively) and no difference between the other values (p>0.05 for all). Conclusion: MRI histogram analysis appears promising as a potential complementary tool for differ-entiating Brucella sacroiliitis from sacroiliitis associated with axSpA; however, these findings are pre-liminary and require confirmation in larger studies.
Keywords: Sacroiliitis; axial spondyloarthritis; histogram analysis; Brucella sacroiliitis